Synthesis and Anti-Mycobacterium tuberculosis Activity of Imidazo[2,1-b][1,3]oxazine Derivatives against Multidrug-Resistant Strains - Fernandes, Guilherme F. S. [UNESP] (2023)
The emergence of multidrug-resistant strains of M. tuberculosis has raised concerns due to the greater difficulties in patient treatment and higher mortality rates. Herein, we revisited the 2-nitro-6,7-dihydro-5H-imidazo[2,1-b][1,3]oxazine scaffold and identified potent new carbamate derivatives having MIC90 values of 0.18–1.63 μM against Mtb H37Rv. Compounds 47–49, 51–53, and 55 exhibited remarkable activity against a panel of clinical isolates, displaying MIC90 values below 0.5 μM. In Mtb-infected macrophages, several compounds demonstrated a 1-log greater reduction in mycobacterial burden than rifampicin and pretomanid. The compounds tested did not exhibit significant cytotoxicity against three cell lines or any toxicity to Galleria mellonella. Furthermore, the imidazo[2,1-b][1,3]oxazine derivatives did not show substantial activity against other bacteria or fungi. Finally, molecular docking studies revealed that the new compounds could interact with the deazaflavin-dependent nitroreductase (Ddn) in a similar manner to pretomanid. Collectively, our findings highlight the chemical universe of imidazo[2,1-b][1,3]oxazines and their promising potential against MDR-TB.